Pengoptimalan Portofolio Saham dengan Capital Asset Pricing Model dan Algoritma Simulated Annealing - Subagja, Rizky Akhmad; Yulianti, Kartika; Agustina, Fitriani (Diophantine Journal of Mathematics and Its Applications, 2025)
Stock investment has become increasingly popular in Indonesia, and the construction of an optimal portfolio is essential for effective risk and return management. This study integrates the Capital Asset Pricing Model (CAPM) with the Simulated Annealing algorithm to optimize stock portfolios. The Simulated Annealing algorithm enables flexible and realistic portfolio management by addressing non-linear complexities and market constraints. In addition, this study develops a Graphical User Interface (GUI)-based application using Python to assist investors in calculating and determining optimal portfolio allocations. The application utilizes stock data and investment parameters as inputs and produces optimal allocation outputs based on CAPM and heuristic solutions generated by the Simulated Annealing algorithm. This research offers an efficient and adaptive solution for portfolio optimization in a fluctuating market environment.